The importance of plasma ferritin values in blood donors for the evaluation of body iron store in a five-month period - Elma Ćatović-Baralija; Gorana Ahmetović-Karić; Sabaheta Hasić; Nesina Avdagić; Nermina Babić (Medicinski glasnik, 2020)
Aim: To present haemoglobin and ferritin parameters in donors to highlight the importance of serum ferritin testing for the purpose of evaluating iron depots in order to make recommendations for preserving a population of blood donors. Method: A prospective study was conducted on 80 blood donors divided in two groups: group I (regular donors, n =40) and group II (irregular donors, n=40). Haemoglobin and ferritin were measured twice every 45 days, before two consecutive blood donations. Results: By measuring haemoglobin and ferritin values before donation in both groups, a decrease of initial ferritin value in Group I relative to Group II was observed (without statistical significance). A significant decrease was found between repeated measurements for both parameters in both groups, indicating equal intensity of the decline in value regardless of a donor status. Measurement of ferritin before and after donation revealed statistically significant loss of ferritin in all examinees (p=0.011). The decline in haemoglobin after donation, although significant, did not fall below the reference value for donation in either women or men. Conclusion: Results: indicate the need for periodic monitoring of the plasma value of ferritin in voluntary donors who donate blood more than twice a year and the possible oral supplementation with iron.
Keywords: anaemia; blood; donors; haemoglobin